2-Phenyl-7-(4-pyridylmethylamino)-1,2,4-triazolo[1,5-a][1,3,5]triazin-5(4H)-one - Dolzhenko, Anton; Tan, G.; Dolzhenko, A.; Koh, L.; Chui, W. (Blackwell Munksgaard, 2011)
In the title compound, C16H13N7O, the 1,2,4-triazolo[1,5-a][1,3,5]triazine heterocyclic system is essentially planar (r.m.s. deviation = 0.0375 A). The attached benzene ring lies almost in the mean plane of 1,2,4-triazolo[1,5-a][1,3,5]triazine [dihedral angle = 1.36 (23) deg], while the pyridine ring is turned out of this plane by the aminomethyl bridge [dihedral angle = 69.22 (9) deg]. The amino group H atom is involved in intramolecular hydrogen bonding with a triazole N atom. In the crystal, molecules are connected via C(=O)NH...N hydrogen bonds into C(11) chains parallel to [100]. The amino group H atom acts as a hydrogen-bond donor, forming an NH...O C hydrogen bond with the carbonyl O atom,which links the molecules into C(6) chains running along [011] and [01-1].